Dampak Penggunaan Pinjaman Online (Pinjol) Terhadap Kondisi Psikososial Keluarga: Studi Kasus Kecamatan Bogor Utara Kota Bogor - Nuraini; Ranti Kha Nur Assiva (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
In recent years, online lending services have become a popular alternative for people who need quick funds. However, this ease of access is often accompanied by high risks, such as high interest rates and pressure to repay loans immediately. This study aims to identify and analyze the impact of using online loans on family psychosocial conditions. This research uses a descriptive qualitative method that produces descriptive data in the form of oral and written information from books and journals or information from informants. The results show that the use of online loans has a negative impact on the family's psychosocial condition, including increased stress, mental disorders, decreased physical health and the possibility of deteriorating relationships between family members. Informants also reported mental health problems such as anxiety and depression due to financial pressures. The findings indicate the need for interventions and education on financial management as well as increased regulation of online lending services to protect the psychosocial well-being of families.